2010
DOI: 10.2165/11315990-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Medications and Risk of Hospitalization in Retirees

Abstract: Background and objective-One important health outcome of inappropriate medication use in elderly is risk of hospitalization. We examined this relationship over 3 years in a retiree health claims database to determine the strength of this association using alternative definitions of potentially inappropriate medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
57
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 22 publications
9
57
1
2
Order By: Relevance
“…Probably, severe ADRs that lead to hospitalization may be caused by idiosyncratic response or predisposition of older people to develop adverse reactions, not necessarily related to the type of drug used. [22] , after adjusting for the variables age, gender, presence of serious diseases and number of drugs prescribed, found that older people who had used PIM were 1.8 to 1.9 times more likely to be hospitalized. Our finding shows that gender and age was not a risk factor for the occurrence of ADR to PIM, and corroborates the results of studies performed by Gallagher et al (2008) [8] and Akazawa et al (2010) [11] , since age categories had no association with PIM use.…”
Section: Discussionmentioning
confidence: 97%
“…Probably, severe ADRs that lead to hospitalization may be caused by idiosyncratic response or predisposition of older people to develop adverse reactions, not necessarily related to the type of drug used. [22] , after adjusting for the variables age, gender, presence of serious diseases and number of drugs prescribed, found that older people who had used PIM were 1.8 to 1.9 times more likely to be hospitalized. Our finding shows that gender and age was not a risk factor for the occurrence of ADR to PIM, and corroborates the results of studies performed by Gallagher et al (2008) [8] and Akazawa et al (2010) [11] , since age categories had no association with PIM use.…”
Section: Discussionmentioning
confidence: 97%
“…Other researches show that the prevalence of institutionalized older people who take at least one PIM ranges from 27.6% to 46.2% (Ruggiero et al, 2010;Castellar et al, 2007;Azoulay et al, 2005). The prescription of PIM must follow judicious protocols, since their administration may double the odds of hospitalization of elderly people (Albert et al, 2010), as well as the demand for health services (Fick et al, 2008). It can also generate hospital expenses (Akazawa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…International research has shown that older age, low levels of physical performance (Dorr et al, 2006;Li, Chu, Sheu, & Huang, 2011), limitations in activities of daily living (Li, Chang, Wang, & Bai, 2011), comorbidity (Dorr et al, 2006;Landi et al, 2004), potentially inappropriate medications (Albert, Colombi, & Hanlon, 2010), and previous hospital admissions (Landi et al, 2004) are factors related to higher risk of hospitalization. In addition, hospitalization is related to community assistance (Nägga, Dong, Marcusson, Skoglund, & Wressle, 2012) and economic hardship (Landi et al, 2004) as well as psychosocial factors such as life satisfaction, loneliness (Jakobsson, Kristensson, Hallberg, & Midlöv, 2011), and selfrated health (Li, Chang, et al, 2011;Nägga et al, 2012).…”
Section: Introductionmentioning
confidence: 99%